Understanding the refinement of grains in laser surface remelted Al–Cu alloys. (15th March 2020) - Patel, M.N.; Qiu, D.; Wang, G.; Gibson, M.A.; Prasad, A.; StJohn, D.H.; Easton, M.A.
Abstract: The coarse-grained microstructure of laser surface remelted (LSR) Al– x  wt.%Cu ( x  = 2, 5 & 7) is significantly refined by Al–3Ti–1B grain refiner. Epitaxial columnar grain growth at the melt pool boundary is suppressed. A reduction in grain size of about 80% is achieved and more than 25% of added TiB2 particles appear to be activated compared to less than 0.1% being activated during casting. The increased nucleation rate is explained in terms of an increase in thermal undercooling, activating a larger number of nucleants of lower potencies, and a reduction in the size of the nucleation free zone. Graphical abstract: Image, graphical abstract